Allocate carbon for a reason: Priorities are reflected in the 13C/12C ratios of plant lipids synthesized via three independent biosynthetic pathways - Zhou, Youping; Stuart-Williams, H.; Grice, Kliti; Kayler, Z.; Zavadlav, S.; Vogts, A.; Rommerskirchen, F.; Farquhar, G.; Gessler, A. (Pergamon, 2015)
It has long been theorized that carbon allocation, in addition to the carbon source and to kinetic isotopic effects associated with a particular lipid biosynthetic pathway, plays an important role in shaping the carbon isotopic composition (13C/12C) of lipids (Park and Epstein, 1961). If the latter two factors are properly constrained, valuable information about carbon allocation during lipid biosynthesis can be obtained from carbon isotope measurements. Published work of Chikaraishi et al. (2004) showed that leaf lipids isotopic shifts from bulk leaf tissue Δδ13Cbk−lp (defined as δ13Cbulkleaftissue − δ13Clipid) are pathway dependent: the acetogenic (ACT) pathway synthesizing fatty lipids has the largest isotopic shift, the mevalonic acid (MVA) pathway synthesizing sterols the lowest and the phytol synthesizing 1-deoxy-d-xylulose 5-phosphate (DXP) pathway gives intermediate values. The differences in Δδ13Cbk−lp between C3 and C4 plants Δδ13Cbk-lp,C4-C3Δδ13Cbk-lp,C4-C3 are also pathway-dependent: View the MathML sourceΔδ13Cbk-lp,C4-C3ACT > View the MathML sourceΔδ13Cbk-lp,C4-C3DXP > View the MathML sourceΔδ13Cbk-lp,C4-C3MVA.These pathway-dependent differences have been interpreted as resulting from kinetic isotopic effect differences of key but unspecified biochemical reactions involved in lipids biosynthesis between C3 and C4 plants. After quantitatively considering isotopic shifts caused by (dark) respiration, export-of-carbon (to sink tissues) and photorespiration, we propose that the pathway-specific differences Δδ13Cbk-lp,C3-C4Δδ13Cbk-lp,C3-C4 can be successfully explained by C4 − C3 carbon allocation (flux) differences with greatest flux into the ACT pathway and lowest into the MVA pathways (when flux is higher, isotopic shift relative to source is smaller). Highest carbon allocation to the ACT pathway appears to be tied to the most stringent role of water-loss-minimization by leaf waxes (composed mainly of fatty lipids) while the lowest carbon allocation to the MVA pathway can be largely explained by the fact that sterols act as regulatory hormones and membrane fluidity modulators in rather low concentrations.